Factors influencing heterogeneity of radiation-induced DNA-damage measured by the alkaline comet assay - Seidel, Clemens (Radiation oncology, 2012)
To investigate whether different conditions of DNA structure and radiation treatment could modify heterogeneity of response. Additionally to study variance as a potential parameter of heterogeneity for radiosensitivity testing.
Published: 20 April 2012
Gesehen am 28.06.2018